2009
DOI: 10.1002/aic.11726
|View full text |Cite
|
Sign up to set email alerts
|

Capillary forces between two solid spheres linked by a concave liquid bridge: Regions of existence and forces mapping

Abstract: This article focuses on the capillary interactions arising when two spherical particles are connected by a concave liquid bridge. This scenario is found in many situations where particles are partially wetted by a liquid, like liquid films stabilized with nanoparticles. We analyze different parameters governing the liquid bridge: interparticle separation, wetting angle and liquid volume. The results are compiled in a liquid volume-wetting angle diagram in which the regions of existence (stability) or inexisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 29 publications
4
55
0
Order By: Relevance
“…It means that the observed repulsive residual force in the previous relaxation tests 1) is possibly attributed to the repulsive capillary force. As we detected the possibility of repulsive capillary forces in a concave liquid bridge, already noticed in literature in both theoritical [4][5][6][7][8] and experimental approaches.…”
Section: )supporting
confidence: 74%
See 2 more Smart Citations
“…It means that the observed repulsive residual force in the previous relaxation tests 1) is possibly attributed to the repulsive capillary force. As we detected the possibility of repulsive capillary forces in a concave liquid bridge, already noticed in literature in both theoritical [4][5][6][7][8] and experimental approaches.…”
Section: )supporting
confidence: 74%
“…Details of the evaluation process can found elsewhere. 4) From Fig. 5, the capillary force is repulsive for V rel of smaller than 0.03 and wetting angle is below 71.6°.…”
Section: )mentioning
confidence: 89%
See 1 more Smart Citation
“…These measurements were validated by comparing to the volume of the water body approximated as axially symmetric from the area of the projection of the bridge in the images using Pappus-Guldinus theorem for selected separations (Fig. 2c) and to a volume calculated employing a toroidal approximation using current geometric data from image processing (as discussed later) following the formula developed in [43]. The difference between the experiments shown is less than a standard deviation in the measurements.…”
Section: Mass Loss Of Liquid Watermentioning
confidence: 96%
“…The surface tension will determine a specific contact angle of liquid metal or slag on a solid substrate, which ultimately establishes a force balance in a packed bed system. 10) The interaction between solid substrates such as packed beds and liquid materials have been studied by several researchers. [12][13][14][15] Among them, Jeong et al recently found out that the permeability of liquid iron in a coke bed could be enhanced by adding a new liquid material of different phase, namely, slag.…”
Section: Introductionmentioning
confidence: 99%